Investigating the position and relationship between right and good in Nahj al-Balaghah - Seyyed Morteza Hosseini; Meysam Kohantorabi (اخلاق وحیانی)
The independent or intertwined definition of the two keywords Right and Good and the precedence of one over the other has been a long-standing and challenging issue in the theoretical field of moral philosophy. Various and sometimes contradictory ideas and moral schools have been established among the early and modern thinkers through different views on this fundamental issue of moral norms. Using a descriptive-analytical method the study shows that the conduct of the Imam, as a genuine Islamic criterion, has been based on the first principle of rule of law as it rejects the sacred view toward the government and provides a model of earthly governance. The righteous conduct of the Imam sometimes complies and other times seems in conflict with good. Some examples of the conflict between right and good in Nahj al-Balaghah include the right to life, the right to equality, the right to political freedoms such as freedom of criticism and protest, the choice of the ruler, the type of government, and renewal of allegiance to the ruler. The precedence of the right over the good is manifested in times of conflict, with the essential and rational support of awareness that leads to individual and collective good. Besides, the manner of Imam Ali (PBUH) in obliging the righteous conduct and explicitly or implicitly recommending goodness reveals his philosophy of Quranic action to achieve the ultimate goal of human creation, which is perfection through the originality of the good.